STUDENT’S PROBLEM IN WRITING UNITY OF PARAGRAPH IN ENGLISH EDUCATION PROGRAM AT MUHAMMADIYAH UNIVERSITY OF BENGKULU - Feti Yuhariah (Teaching English and Language Learning English Journal, 2022)
The objective of this research was to identify the Student’s Problem in Writing Unity of Paragraph in English Education Program at Muhammadiyah University of Bengkulu who have followed writing II subject. This study use qualitative research, and used descriptive qualitative method. The subject of this research was consisted of 28 students fourt semester. In this research, the researcher used scoring criteria Unity of Paragraphs as instrument and using three different topic get the data. The data were collected by: Asking students to write paragraph descriptive with different topics. In identified and classified the students problem in writing unity of paragraphs to gave the score based on Oshima and Hogue (1983) criteria. The result of this research, the Student’s Problem in Writing Unity of Paragraph in English Education Program at Muhammadiyah University of Bengkulu still poor in write: the use of Trasition Signal (TS), Supporting Sentences (SS), and Concluding Sentences (CS). This research suggested the students to study and practice more in the use of transition signal, Supporting Sentences, Concluding Sentences therefore the students could write good unity of paragraph. Keywords: Writng, Unity, Paragraph.